Human MxA Protein Confers Resistance to Semliki Forest Virus and Inhibits the Amplification of a Semliki Forest Virus-Based Replicon in the Absence of Viral Structural Proteins - Landis, Heinrich (American Society for Microbiology, 1998)
Mx proteins form a small family of interferon (IFN)-induced GTPases with potent antiviral activity against various negative-strand RNA viruses. To examine the antiviral spectrum of human MxA in homologous cells, we stably transfected HEp-2 cells with a plasmid directing the expression of MxA cDNA. HEp-2 cells are permissive for many viruses and are unable to express endogenous MxA in response to IFN. Experimental infection with various RNA and DNA viruses revealed that MxA-expressing HEp-2 cells were protected not only against influenza virus and vesicular stomatitis virus (VSV) but also against Semliki Forest virus (SFV), a togavirus with a single-stranded RNA genome of positive polarity. In MxA-transfected cells, viral yields were reduced up to 1,700-fold, and the degree of inhibition correlated well with the expression level of MxA. Furthermore, expression of MxA prevented the accumulation of 49S RNA and 26S RNA, indicating that SFV was inhibited early in its replication cycle. Very similar results were obtained with MxA-transfected cells of the human monocytic cell line U937. The results demonstrate that the antiviral spectrum of MxA is not restricted to negative-strand RNA viruses but also includes SFV, which contains an RNA genome of positive polarity. To test whether MxA protein exerts its inhibitory activity against SFV in the absence of viral structural proteins, we took advantage of a recombinant vector based on the SFV replicon. The vector contains only the coding sequence for the viral nonstructural proteins and the bacterial LacZ gene, which was cloned in place of the viral structural genes. Upon transfection of vector-derived recombinant RNA, expression of the β-galactosidase reporter gene was strongly reduced in the presence of MxA. This finding indicates that viral components other than the structural proteins are the target of MxA action.